2020
DOI: 10.3892/etm.2020.8676
|View full text |Cite
|
Sign up to set email alerts
|

In�vitro differentiation of rhesus macaque bone marrow‑ and adipose tissue‑derived MSCs into hepatocyte‑like cells

Abstract: Orthotopic liver or hepatocyte transplantation is effective for the treatment of acute liver injury and end-stage chronic liver disease. However, both of these therapies are hampered by the extreme shortage of organ donors. The clinical application of cell therapy through the substitution of hepatocytes with mesenchymal stem cells (MSCs) that have been differentiated into hepatocyte-like cells (HLCs) for liver disease treatment is expected to overcome this shortage. Bone marrow and adipose tissue are two major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…16,17 Despite being found in a variety of tissues, MSCs share comparable phenotypic characteristics, and some may even have extra features that are indicative of the source tissues. [17][18][19] MSCs can transform into a minimum of three different cell types, namely, adipocytes, chondrocytes, and osteocytes. 19,20 Because MSCs are able to distinguish, their use in clinical trials has expanded substantially.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Despite being found in a variety of tissues, MSCs share comparable phenotypic characteristics, and some may even have extra features that are indicative of the source tissues. [17][18][19] MSCs can transform into a minimum of three different cell types, namely, adipocytes, chondrocytes, and osteocytes. 19,20 Because MSCs are able to distinguish, their use in clinical trials has expanded substantially.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] MSCs can transform into a minimum of three different cell types, namely, adipocytes, chondrocytes, and osteocytes. 19,20 Because MSCs are able to distinguish, their use in clinical trials has expanded substantially. 21 MSCs are now well recognized as a type of precursor cells that support the stroma and have the ability to differentiate into stroma-supporting cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLCs are cells with similar functions and characteristics to normal hepatocytes. It has been proved in vitro and in vivo that MSCs could be induced to differentiate into HLCs and express hepatocyte specific markers, such as albumin (ALB) [7,8]. Recent studies have revealed that MSCs can alleviate hepatic injury, improve hepatic function, and promote liver tissue regeneration and repair.…”
Section: Introductionmentioning
confidence: 99%
“…A potential alternative to primary hepatocytes is hepatocyte‐like cells derived from mesenchymal stem cells, which are capable of differentiating into most mesodermal cell types, as well as endodermal cell types (Spees et al., 2016; Wang et al., 2020). Cultured mesenchymal stem cells are of advantage in that they can be obtained in high quantities without losing their multipotency, in comparison with nonproliferative hepatocytes.…”
Section: Introductionmentioning
confidence: 99%